Pemanfaatan Drum Bekas Menjadi Tempat Sampah Di Kelurahan Betungan - Bentara, Julian; Nasution , Muhammad Fajar; lIlahi, Muhammad Dandi; Alisah, Siti; Sari, Yosita Tri Purnama; Azhari , Diah; Mujiono, Mujiono; Fariadi, Herri (Universitas Dehasen Bengkulu, 2025)
Environmental cleanliness is an important aspect in creating a healthy and comfortable quality of life for the community. One of the main problems that affects cleanliness is ineffective waste management, many people do not have full awareness in disposing of waste in its place, thus causing environmental pollution. To overcome this, the implementation of the 3R principle (reduce, Reuse, Recycle) is the right solution in managing waste sustainably. One effort that can be made is to utilize used drums as economical and environmentally friendly trash bins. This innovation not only reduces waste but also increases public awareness of the importance of maintaining environmental cleanliness. The community welcomes the provision of trash bins in their residential areas.